Supervision of Village Funds by Local GovernmentMerauke Regency (Study in Jagebob District, Merauke Regency) - Frien’s Bernard Kramayir; Petrus Polyando; Devi Irena (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
Study This aim For analyze form, mechanism, and effectiveness supervision Village Fund budget carried out by the Merauke Regency Regional Government, with focus on implementation in the District Jagebob. Supervision of Village Funds becomes aspect important in realizing governance​ transparent, accountable, and welfare - oriented government village community. District Jagebob chosen Because is one of the areas with sufficient number of villages many and facing diverse challenge in distribution as well as utilization of village funds, especially related capacity apparatus and coordination between party Research manager​ This use method descriptive qualitative with approach studies case. Data collected through interviews, observations, and documentation to apparatus government regional, village heads, as well village assistant. Data analysis was carried out through data reduction, data presentation, and data extraction conclusion in a way interactive. Research results show that mechanism supervision Village Fund budget in the District Jagebob walk through four stages main, namely determination standard, measurement implementation, evaluation with compare results to standards and actions corrective. Practice implementation in the field Not yet completely optimal, characterized by non-conformity guidelines with condition real, limitations capacity apparatus, documents that are not incomplete, incomplete evaluation​ consistent, and action slow and ineffective corrective action always proportional. Supervision supported by clear guidelines, coaching​ routine and commitment government area, however Still hampered by weak coordination, limited human resources, number of minimal supervision, and conditions difficult geography​ reachable.